Comparison of Burn Depth at Different Temperatures on Ex Vivo Human Skin with Standardized Model and Comparison of the Results with Rat Contact Burn Model - Mehmet Surhan Arda; Nilsun Kuas; Erdem Söztutar; Atacan Emre Koçman; Hüseyin İlhan (Galenos Yayinevi, 2018)
Aim: Burns are still an important mortality and morbidity problem worldwide. Clinical studies are limited, owing to ethical concerns and an inability to achieve standardization. Therefore, studies are concentrated on experimental models. However, there are still a lot of questions that await resolution. Additionally, the relevance of animal models on human skin (HS) is unknown. From this point of view, this study aims to evaluate the depth of burn on ex vivo HS and to compare the HS results with those of rats. Materials and Methods: Skins of patients, after obtaining informed consent, that underwent full thickness healthy skin excision (abdominoplasty), except for experimental purposes, have been included. A total of three different temperatures (60, 80 and 100 °C) using two different weight forces (0.88 kg/cm2 for high and 0.21 kg/cm2 for low) using standardized apparatus facilitated the formation of study groups. In all groups, healthy dermis-epidermis burn depth was compared. Results: No difference was detected between healthy HS depths from the various samples taken from different donors that were to be tested. The lowest result (10.5±0.7% burn depth ) was seen in the 60 °C low weight force group and the highest was seen in the 100 °C high weight force group (92.0±2.7). As for the 80 °C high pressure group vs the 100 °C low pressure groups, a significant difference was noted. Conclusion: Ex vivo HS can be used as an experimental burn model. It has been shown that standardized depth of burn can be achieved using standardized apparatus. However, the different depth of burn indicates that control of parameters (pressure, time, temperature) is mandatory.